Photoinduced hidden monoclinic metallic phase of VO2 driven by local nucleation - Feng-Wu Guo; Wen-Hao Liu; Zhi Wang; Shu-Shen Li; Lin-Wang Wang; Jun-Wei Luo (Nature Communications)
Abstract The insulator-to-metal transition in VO2 has garnered extensive attention for its potential applications in ultrafast switches, neuronal network architectures, and storage technologies. However, the photoinduced insulator-to-metal transition remains controversial, especially whether a complete structural transformation from the monoclinic to rutile phase is necessary. Here we employ the real-time time-dependent density functional theory to track the dynamic evolution of atomic and electronic structures in photoexcited VO2, revealing the emergence of a long-lived monoclinic metal phase under low electronic excitation. The emergence of the metal phase in the monoclinic structure originates from the dissociation of the local V-V dimer, driven by the self-trapped and self-amplified dynamics of photoexcited holes, rather than by an electron-electron correction. On the other hand, the monoclinic-to-rutile phase transition does appear at higher electronic excitation. Our findings validate the existence of monoclinic metal phase and provide a comprehensive picture of the insulator-to-metal transition in photoexcited VO2.